On the Seaweeds from the Coast of Lutzow-Holm Bay, Antarctica - Masao OHNO (National Institute of Polar Research, 1976)
This paper is a note on the Antarctic seaweeds collected from the coast of Liitzow-Holm Bay in January 1975. A specimen of Desmarestia sp. (Fig. 1) was found washed ashore on the coast of Langhovde (Lat. 69°14'S, Long. 39°44'E). Antarctic red algae, Phyllophora antarctica A. et E. S. GEPP and Phycodrys antarctica (SKOTTSBERG) SKOTTSBERG (Fig. 2) was collected from beneath the ice on the coast of East Ongul Island (Lat. 69°S, Long. 39°35'E). The water temperature of the habitat was -0.5℃. The light intensity was 650 lx. Phyllophora antarctica A. et E. S. GEPP GEPP and GEPP, 1905, p. 109 1907, p. 15 SKOTTSBERG, 1953, p. 558 NEUSHUL, 1968, pl. 4. Type location : Victoria Land. Distribution : Macrobertson Coast, Adelie Coast, Victoria Land Phycodrys antarctica (SKOTTSBERG) SKOTTSBERG SKOTTSBERG, 1923, p. 35 1953, p. 548 and 562. Type location : Antarctic Peninsula. Distribution : Antarctic Peninsula, Adelie Coast, Macrobertson Coast.